Ultrasound-assisted liquid biphasic extraction of fucoidan from Sargassum sp. - Boy Arief Fachri; Jovita Labibah; Zakia Luthfiana; Ansori Ansori; Ditta Putri (Universitas Lambung Mangkurat, 2026)
Sargassum sp.. is an essential source of fucoidan. This work aims to extract fucoidan from Sargassum sp.. using a liquid biphasic system assisted by ultrasonics. It observes the effects of various process parameters on fucoidan yield, determines the optimum extraction conditions, and develops a model for extraction kinetics. In the experiment, 80-mesh Sargassum sp.. powder is ultrasonically treated in a 2-propanol solution. Furthermore, the extract is separated by the addition of a K₂HPO₄ solution, which forms a two-phase system. Following the process, the CaCl2 is introduced to separate the alginate. Afterwards, ethanol is added to the resulting filtrate to precipitate fucoidan. This approach highlights techniques for efficient extraction and separation of fucoidan from Sargassum sp.. The process parametperaturaers included extraction time (10, 15, and 20 minutes), ultrasonic power (60%, 65%, and 70%), and the Sargassum-to-solvent ratio (0.03, 0.04, and 0.05 g/mL). This work confirms that FTIR and HPLC techniques successfully identified fucoidan. The highest yield, 14.1%, was achieved with a Sargassum-to-solvent ratio of 0.04 g/mL, an extraction time of 20 minutes, and an ultrasonic power of 70%. The results indicate that extraction time is a significant factor compared to power and the Sargassum-to-solvent ratio. The diffusion coefficient (Dₑ) of 1.425118 × 10⁻² m²/s suggests relatively rapid diffusion under the applied extraction conditions.